The Future of Just War New Critical Essays - Gentry, Caron E.; Eckert, Amy E. (Studies in Security and International Affairs, 2014)
These essays seek to reorient the Just War tradition around its core concerns of preventing the unjust use of force by states and limiting the harm inflicted on vulnerable populations such as civilian noncombatants. Contributors argue that the tradition needs to be updated to deal with substate actors within the realm of legitimate authority, private military companies, and the questionable moral difference between the use of conventional and nuclear weapons. Additionally, as recent policy makers and scholars have tried to make the Just War criteria legalistic, they have weakened the tradition's ability to draw from and adjust to its contemporaneous setting.